Prognostic Value and Molecular Mechanisms of Proteasome 26S Subunit, Non-ATPase Family Genes for Pancreatic Ductal Adenocarcinoma Patients after Pancreaticoduodenectomy - Caifu Zhou; Haixia Li; Xiao Han; Hongbing Pang; Manya Wu; Yanping Tang; Xiaoling Luo (Journal of Investigative Surgery, 2022)
Objective: Pancreatic cancer (PC) is an extremely malignant tumor with similar morbidity and mortality and lack of an effective treatment. This study explored the prognostic value and molecular mechanisms of proteasome 26S subunit, non-ATPase (PSMD) family genes in pancreatic ductal adenocarcinoma (PDAC). Methods: Survival analyses were performed to elucidate the relationship between prognosis and the level of PSMD expression. ROC curves and nomograms were constructed to predict the prognosis. A bioinformatics analysis was used to explore the co-expression and complex interaction networks of PSMDs. The potential mechanisms were further explored via gene set enrichment analysis (GSEA). Results: We find high levels of PSMD6, PSMD9, PSMD11, and PSMD14 expression were significantly associated with a poorer OS. High PSMD6 and PSMD11 expression was associated with a poorer relapse-free survival (RFS). A risk score model was constructed based on prognosis-related genes. The area under ROC curves (AUC) was 53.3%, 59.3%, and 62.9% for 1-, 2-, 3 years, respectively. Conclusion: GSEA revealed that PSMD6 and PSMD11 play a role in PDAC through various biological processes and signaling pathways, including TP53, CDKN2A, MYC pathway, DNA repair, KRAS, cell cycle checkpoint, NIK, NF-κB signaling pathway, and proteasomes. This study demonstrated that PSMD6 and PSMD11 could serve as a potential prognostic and diagnostic biomarkers for patients with early-stage PDAC after pancreaticoduodenectomy.